Peningkatan Kompetensi Guru RA Se-Kota Tanjungpinang dalam Mengembangkan Fundamental Motor Skills Anak Usia Dini Melalui Strategi Pembelajaran Rangkaian Permainan - Nadya Nela Rosa; Nisrina Nuraini; Dilvia Suriski Rahmayani; Lina Eka Retnaningsih (Universitas Islam Lamongan, 2025)
The improvement of Fundamental Motor Skills (FMS) in early childhood can be achieved through the effective implementation of Play-Based Learning Strategies by RA teachers in Tanjungpinang City. This study aims to enhance the Fundamental Motor Skills (FMS) of early childhood students through the application of Play-Based Learning Strategies by RA teachers in Tanjungpinang City. The method applied in this community service program is Participatory Action Research (PAR). RA teachers who participated in the training gained new knowledge and understanding of the fundamental concepts of early childhood Fundamental Motor Skills (FMS), including proper forms and movements that can be appropriately stimulated in their respective schools. In addition, they acquired insights into play-based learning strategies and skills to implement these strategies effectively. The new strategies are designed with a fun play-based approach, which not only helps develop children's FMS but also increases their enthusiasm. The implementation of Play-Based Learning Strategy training for RA teachers in Tanjungpinang City has been deemed effective in supporting the development of Fundamental Motor Skills (FMS) in early childhood. Given the importance of FMS development, these strategies assist teachers in facilitating learning effectively.